Are There Any Differences Of Learning Orientation Between Leve 1 And Level 4 Nursing Students - Fatikhu Yatuni Asmara (Jurnal Manajemen Keperawatan, 2014)
Purpose: The aim of this research is to identify the differences of learning orientation between level 1 and level 4 nursing students. Method: Data were collected using Inventory of Learning Styles (ILS) questioners which involved two students as respondents, level 1 and level 4 nursing students. The data were calculated based on scoring key in each sub component, and were compared with standard of psychology students. Result: The result showed that there were differences of learning orientation between level 1 and level 4 nursing students particularly in components personally interested, certificate directed, vocation directed, and ambivalent. One of reasons behind of this is level 1 nursing students get transition from senior high school into college while level 4 nursing students are settler, and can adapt with learning process in college. Conclusion: It will be better if every student has change to screen their learning orientation by completing ILS questioners, so it will help students to focus on their learning process on the other hand, students’ learning orientation will help teacher to facilitate students achieving the competencies.